Accelerated peptide bond formation at air–water interfaces - Deming Xia; Fanqi Zeng; Wanting Chen; Hui Zhao; Hong-Bin Xie; Jingwen Chen; Joseph S. Francisco (Proceedings of the National Academy of Sciences, 2025)
Peptides and proteins, essential components of living organisms, are composed of amino acids linked by peptide bonds. However, the mechanism of peptide bond formation during the prebiotic era remains unclear. In this study, advanced Born–Oppenheimer molecular dynamics (BOMD) simulations were used to investigate the mechanisms and kinetics of peptide bond formation at air–water interfaces using diglycine, the simplest dipeptide, as a model molecule. The results show that peptide bonds can be rapidly formed via a unique isomerization-then-OH − -elimination pathway. In this mechanism, the diglycine initially isomerizes into its acidic form at the air–water interface, followed by a reaction that releases an OH − anion rather than the previously hypothesized H 2 O. The free-energy barriers for the interfacial pathway with the assistance of an interfacial electric field are much lower than those in the gas phase by >25 kcal/mol. Further calculations suggest that this mechanism can be extended to the formation of some larger peptides, such as tetraglycine. This pathway offers insights into the origin of life and could inform the development of methods for peptide synthesis.